‘Vaccine as a cheat sheet’: a metaphor gone awry on Facebook - Negrea-Busuioc, Elena (Frontiers in Psychology, 2023)
COVID-19 vaccine-related conspiracy narratives skyrocketed in social media in the first year of the pandemic. Science communicators have tried to debunk false information as did Vlad Mixich, a Romanian public health expert, who used the metaphor 'vaccine as a cheat sheet' to explain on Facebook why the vaccine cannot modify the human DNA. Additionally, Mixich used the 'cheating' metaphor as a part of a mockery targeting people susceptible to false information. This paper examines the conceptual clarification and mocking functions of the 'vaccine as a cheat sheet' deliberate metaphor and shows that while it simplifies abstract knowledge and allows the audience to engage with a complex topic, this metaphor also amplifies vaccine-related polarization.